Pengaruh Gaya Kepemimpinan Terhadap Efektivitas Kerja Pegawai di Kantor Desa Biringala Kecamatan Barombong Kabupaten Gowa - Adawiyah, St Nur Raudhatul; Tahir, Muhammad; Arfah, Sitti Rahmawati (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to determine how much influence leadership has on employee work effectiveness at the Biringala Village Office, Barombong District, Gowa Regency. This type of research is quantitative, while the number of samples used in this study is 50 respondents. Data collection techniques used in this study were questionnaires and documentation. The data analysis technique used is simple linear regression analysis. The data validation technique was obtained through validation tests and reliability tests. The results of this study indicate that leadership style has a positive and significant effect on the work effectiveness of employees at the Biringala village office, Barombong sub-district, Gowa district. Based on the output of the summary model, it can be seen that the magnitude of the regression value (R) or influence is 0.460 and is positive. While the value of R Square is 0.212. So it can be concluded that the variable X (Leadership Style) has an influence of 21.2% on the Y variable (Employee Work Effectiveness) and the remaining 78.8% is influenced by other factors. Which means that the leadership style at the Biringala Village office is quite good in increasing the effectiveness of the employee's work, while there is an influence from other factors besides the leadership style of 78.8% which can affect the effectiveness of the employee's work at the Biringala village office.